\(\displaystyle \bold{d.}\)
\(\displaystyle \mathcal{L}\{\cos \omega t \ u(t)\} = \int_{0}^{\infty} \cos \omega t \ u(t) e^{-st} \ dt = \int_{0}^{\infty} \cos \omega t \ e^{-st} \ dt\)
Let us this time solve this integral by integration by parts.
\(\displaystyle u = \cos \omega t\)
\(\displaystyle du = -\omega\sin \omega t \ dt\)
\(\displaystyle dv = e^{-st} \ dt\)
\(\displaystyle v = \frac{1}{-s}e^{-st}\)
\(\displaystyle \int_{0}^{\infty} \cos \omega t \ e^{-st} \ dt = \frac{1}{-s}e^{-st}\cos \omega t\bigg |_{0}^{\infty} - \frac{\omega}{s}\int_{0}^{\infty} \sin \omega t e^{-st} \ dt\)
\(\displaystyle = \frac{1}{-s}\left(0 - 1\right) - \frac{\omega}{s}\int_{0}^{\infty} \sin \omega t e^{-st} \ dt = \frac{1}{s} - \frac{\omega}{s}\int_{0}^{\infty} \sin \omega t e^{-st} \ dt\)
\(\displaystyle u = \sin \omega t\)
\(\displaystyle du = \omega\cos \omega t \ dt\)
\(\displaystyle dv = e^{-st} \ dt\)
\(\displaystyle v = \frac{1}{-s}e^{-st}\)
\(\displaystyle \frac{1}{s} - \frac{\omega}{s}\int_{0}^{\infty} \sin \omega t e^{-st} \ dt = \frac{1}{s} + \frac{\omega}{s^2}e^{-st}\sin \omega t \bigg |_{0}^{\infty} - \frac{\omega^2}{s^2}\int_{0}^{\infty} e^{-st}\cos \omega t \ dt\)
\(\displaystyle = \frac{1}{s} + \frac{\omega}{s^2}(0 - 0) - \frac{\omega^2}{s^2}\int_{0}^{\infty} e^{-st}\cos \omega t \ dt = \frac{1}{s} - \frac{\omega^2}{s^2}\int_{0}^{\infty} e^{-st}\cos \omega t \ dt\)
\(\displaystyle \left(1 + \frac{\omega^2}{s^2}\right)\int_{0}^{\infty} \cos \omega t \ e^{-st} \ dt = \frac{1}{s}\)
\(\displaystyle \int_{0}^{\infty} \cos \omega t \ e^{-st} \ dt = \frac{1}{s\left(1 + \frac{\omega^2}{s^2}\right)} = \frac{1}{s\left(\frac{s^2}{s^2} + \frac{\omega^2}{s^2}\right)} = \frac{s^2}{s\left(s^2 + \omega^2\right)} = \frac{s}{s^2 + \omega^2}\)